Vitamin D-mediated modifications in protein-DNA interactions at two promoter elements of the osteocalcin gene. - Markose, E R (1990)
By the combined use of DNase I footprinting, electrophoretic mobility-shift assay, and methylation interference analysis, we have identified a series of sequence-specific protein-DNA interactions in the 5' flanking region of the rat osteocalcin gene. Stimulation of osteocalcin gene expression by 1,25-dihydroxyvitamin D3, a physiologic mediator of this bone-specific gene in vitro and in vivo, is associated with modifications in the binding of ROS 17/2.8 cell nuclear factors to two promoter segments that up-regulate transcription. One segment located between -462 and -437 exhibits a vitamin D-dependent increase in sequence-specific binding of nuclear factors. This element (CTGGGTGAATGAGGACATTACTGACC), identified at single nucleotide resolution, contains a region of hyphenated dyad symmetry and shares sequence homology with consensus steroid-responsive elements and with the sequence that has been identified as the vitamin D receptor binding site in the human osteocalcin gene. We have also observed that vitamin D stimulation of osteocalcin gene expression results in a 5-fold increase in protein binding to the region of the osteocalcin box, a 24-nucleotide segment in the proximal promoter with a CCAAT motif as the central core. Our results demonstrate protein-DNA interactions in a vitamin D-responsive element and in a second sequence, the osteocalcin box, both of which are involved in the physiologic regulation of the osteocalcin gene in response to 1,25-dihydroxyvitamin D3.